3D molecular structure analysis of NS2B/NS3 proteases derived from dengue virus and Zika virus - Arli Aditya Parikesit; Stefanus Bernard (Trends in Infection and Global Health, 2022)
Both dengue and Zika viruses have infected millions of people worldwide, urging the development of efficacious drugs and vaccines to fight the infection. Unfortunately, current research is yet to elucidate the structural proteomics comparison of the NS2B/NS3 from both viruses. Therefore, the main objective of this study was to comparatively study the structural proteins between dengue and Zika viruses by leveraging standard homology modelling tools. Our data provide 3D molecular structure overviews of NS2B/NS3 derived from the foregoing viruses. Sequence alignment indicated that the viruses share a 56% similarity rate of protein structures. However, in terms of function, both have NS2B that is pivotal for the activation of NS3 proteases.